Detecting Infections Rapidly and Easily for Candidemia Trial (DIRECT1): A Prospective, Multicenter Study of the T2Candida Panel. (4th October 2017) - Clancy, Cornelius J; Pappas, Peter; Vazquez, Jose; Judson, Marc A; Tobin, Ellis; Kontoyiannis, Dimitrios P; Thompson, George R; Reboli, Annette; Garey, Kevin W; Greenberg, Richard N; Ostrosky-Zeichner, Luis; Wu, Alan; et al.
Abstract: Background: Blood cultures (BC) are the diagnostic gold standard for candidemia, but sensitivity is <50%. T2 Candida (T2) is a novel, FDA-approved nanodiagnostic panel, which utilizes T2 magnetic resonance and a dedicated instrument to detect Candida within whole blood samples. Methods: Candidemic adults were identified at 14 centers by diagnostic BC (dBC). Follow-up blood samples were collected from all patients (pts) for testing by T2 and companion BC (cBC). T2 was run-in batch at a central lab; results are reported qualitatively for three groups of spp. ( Candida albicans/C. tropicalis (CA/CT), C. glabrata/C. krusei (CG/CK), or C. parapsilosis (CP)). T2 and cBC were defined as positive (+) if they detected a sp. identified in dBC. Results: 152 patients were enrolled (median age: 54 yrs (18–93); 54% (82) men). Candidemia risk factors included indwelling catheters (82%, 125), abdominal surgery (24%, 36), transplant (22%, 33), cancer (22%, 33), hemodialysis (17%, 26), neutropenia (10%, 15). Mean times to Candida detection/spp. identification by dBC were 47/133 hours (2/5.5 d). dBC revealed CA (30%, 46), CG (29%, 45), CP (28%, 43), CT (11%, 17) and CK (3%, 4). Mean time to collection of T2/cBC was 62 hours (2.6 d). 74% (112) of patients received antifungal (AF) therapy prior to T2/cBC (mean: 55 hours (2.3 d)). Overall, T2 results were more likely than cBC to be + ( P < 0.0001; Table), a result driven by performance in AF-treated patients ( P < 0.0001). T2 was more likely to be + among patients originally infected with CA (61% (28) vs. 20% (9); P = 0.001); there were trends toward higher positivity in patients infected with CT (59% (17) vs. 23% (4; P = 0.08) and CP (42% (18) vs. 28% (12); P = 0.26). T2 was + in 89% (32/36) of patients with + cBC. Conclusion: T2 was sensitive for diagnosing candidemia at the time of + cBC, and it was significantly more like to be + than cBC among AF-treated patients. T2 is an important advance in the diagnosis of candidemia, which is likely to be particularly useful in patients receiving prophylactic, pre-emptive or empiric AF therapy. Disclosure: D. P. Kontoyiannis, Pfizer: Research Contractor, Research support and Speaker honorarium; Astellas: Research Contractor, Research support and Speaker honorarium; Merck: Honorarium, Speaker honorarium; Cidara: Honorarium, Speaker honorarium; Amplyx: Honorarium, Speaker honorarium; F2G: Honorarium, Speaker honorarium; L. Ostrosky-Zeichner, Astellas: Consultant and Grant Investigator, Consulting fee and Research grant; Merck: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium; Pfizer: Grant Investigator and Speaker's Bureau, Grant recipient and Speaker honorarium; Scynexis: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; Cidara: Grant Investigator and Scientific Advisor, Consulting fee and Research grant; S. Apewokin, T2 biosystems: Investigator, Research support; Astellas: Scientific Advisor, Consulting fee